Anti‐adipogenesis and metabolism‐regulating effects of heat‐inactivated Streptococcus thermophilus MN‐ZLW‐002. (1st June 2021) - Kang, X.; Liang, H.; Luo, Y.; Li, Z.; He, F.; Han, X.; Zhang, L.
Abstract: Metabolic syndrome and obesity have become serious threats to public health worldwide. This study was conducted to evaluate the anti‐adipogenesis and metabolism‐regulating effects of heat ‐ inactivated Streptococcus thermophilus MN‐ZLW‐002 (MN‐ZLW‐002), which can be used as a yogurt starter. In vitro study suggested that MN‐ZLW‐002 stimulated the RAW264.7 macrophages to produce significant amounts of interleukin (IL)‐6, IL‐10 and tumour necrosis factor (TNF)‐α and induced intense phosphorylation of P38, p44/42 MAPK and nuclear factor κB. MN‐ZLW‐002‐stimulated RAW264.7‐conditioned medium (CM) notably suppressed the differentiation and adipogenesis of 3T3‐L1 pre‐adipocytes. The 12‐week in vivo study suggested that orally administered MN‐ZLW‐002 significantly reduced the weight gain of mice caused by the high‐fat diet (HFD) at weeks 3–8; decreased fasting blood glucose levels at week 4 and week 8; decreased serum total triglyceride level at week 12. MN‐ZLW‐002 also reduced serum IL‐1β and chemokine ligand 3 levels in the HFD‐fed mice. These findings suggest that heat‐inactivated MN‐ZLW‐002 can suppress adipocytes differentiation and lipid accumulation by regulating the immune response, possibly via the release of cytokines, particularly TNF‐α; MN‐ZLW‐002 can improve metabolism‐related indicators in the early stage of HFD intervention and regulate the related pro‐inflammatory immune response. Significance and Impact of the Study: This study is the first to demonstrate that Streptococcus thermophilus, a strain widely used in the dairy industry as a yogurt starter, even in the state of inactivated, has the potential to prevent obesity by stimulating immune cells and, thus, inhibiting pre‐adipocytes differentiation. In vivo study also showed the potential metabolism‐regulating effects of heat‐inactivated S. thermophilus .